2011
DOI: 10.1080/13803395.2011.614597
|View full text |Cite
|
Sign up to set email alerts
|

Information processing speed, neural efficiency, and working memory performance in multiple sclerosis: Differential relationships with structural magnetic resonance imaging

Abstract: Multiple sclerosis (MS), a central nervous system (CNS) neurodegenerative disorder, involves lesions of both white and gray matter and reported cognitive impairments that include processing speed (PS), executive function, and working memory (WM). This study closely examined the specifics of these cognitive deficits and their relationship to structural brain damage. A visual n-back task with 3 WM load conditions was used to assess WM performance (task accuracy), PS (reaction time, RT), and a novel measure of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 66 publications
(87 reference statements)
1
29
0
1
Order By: Relevance
“…33,43 The results are also consistent with prior studies showing that subjects with MS perform significantly worse than HCs on cognitive tests assessing processing speed, working and visual-spatial processing/memory, sustained attention, and executive function. 21,[44][45][46] The diffuse SLE syndromes such as anxiety disorders, mood disorders, headache, and cognitive impairment may be the result of diffuse damage, whereas focal SLE syndromes such as seizures, strokes, and transient ischemic attacks, result in high-attenuation focal lesions. Several studies have shown regionally-specific decreased FA and increased MD in patients with NPSLE compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…33,43 The results are also consistent with prior studies showing that subjects with MS perform significantly worse than HCs on cognitive tests assessing processing speed, working and visual-spatial processing/memory, sustained attention, and executive function. 21,[44][45][46] The diffuse SLE syndromes such as anxiety disorders, mood disorders, headache, and cognitive impairment may be the result of diffuse damage, whereas focal SLE syndromes such as seizures, strokes, and transient ischemic attacks, result in high-attenuation focal lesions. Several studies have shown regionally-specific decreased FA and increased MD in patients with NPSLE compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…One indication of this problem lies in the interaction between the alerting network and executive control network seen in the present study and in others (Crivelli et al, 2012;McConnell, & Shore, 2011;Urbanek et al, 2010). But a broader rendition of this issue is suggested by the "complexity effect," the frequent observation that the disparity between MS patients and controls in terms of processing speed increases with the complexity of the information processing task they are called upon to execute (Covey, Zivadinov, Shucard, & Shucard, 2011;Hughes et al, 2011;Kujala et al, 1994;Lengenfelder et al, 2006;Parmenter, Shucard, & Shucard, 2007;Reicker et al, 2007). With its complicated array of warning cues and flankers varying on each trial, the ANT has to be counted as one of the more complex tests being used in MS research, and the impact of this complexity on the differences observed between MS patients and controls is not well understood.…”
Section: Processing Speed and Attention In Msmentioning
confidence: 59%
“…This was evident in the small error rates made by both the MS and control groups. A more cognitively demanding visual processing task may tax cognitive reserves and require a higher degree of neural efficiency and, consequently, unmask underlying visuoperceptual and visual processing speed deficits (Covey, Zivadinov, Shucard, & Shucard, 2011). Consistent with this assumption, De Sonneville and colleagues (2002) found that the difference in processing speed between adults with MS and controls increased drastically as tasks became more cognitively demanding.…”
Section: Response Conflict Effectsmentioning
confidence: 86%